KAJIAN PERSEBARAN KOMODITAS TEH: PENGEMBANGAN KAWASAN PERKEBUNAN TEH DI PROVINSI JAWA BARAT - Basorudin, Muhammad; Rizqi, Aniisa; Murdaningrum, Sri; Maharani, Windi (Jurnal Sosial Ekonomi Pertanian, 2019)
Tea is one of the main commodities that is a mainstay of Indonesian exports and has been exported to 78 countries on five continents. However, the development of the volume of Indonesian tea exports tends to decline from 2011 to 2015. Therefore, this study aims to find out which districts are potential areas and non-potential areas in West Java Province as the largest tea-producing region in Indonesia. Then, to find out the growth rate of tea production in each district in West Java Province and how the area is spread based on its potential. The method used is Location Quotient, Shift Share, and Quadrant Method. Based on the research, it was found that the area that has potential and became the basis so that its construction can contribute significantly to tea plantations in West Java Province are Bandung, Cianjur, Purwakarta, Bandung Barat, Garut, Tasikmalaya, and Sukabumi. Then, the calculation results with this quadrant indicate that the mainstay tea plantation area is in the Sukabumi, Cianjur, Bandung, Garut, and West Bandung regions.